Bribery and extortion in international business: Ethical perceptions of Greeks compared to Americans - Tsalikis, John (Journal of business ethics, 1995)
This study investigates the differences in he way bribery and extortion is perceived by two different cultures — American and Greek. Two hundred and forty American business students and two hundred and four Greek business students were presented with three scenarios describing a businessman offering a bribe to a government official and three scenarios describing a businessman being forced to pay a bribe to an official in order to do business. The Reidenbach-Robin instrument was used to measure the ethical reactions of the two samples to these scenarios. Results indicate that ethical reactions to bribery and extortion vary by (a) the nationality of the person offering the bribe, and (b) the country where the bribe is offered. In addition, Greeks perceived some of the scenarios as being less unethical than did Americans.